Front Cover: The Route from the Folded to the Amyloid State: Exploring the Potential Energy Surface of a Drug‐Like Miniprotein (Chem. Eur. J. 9/2020). Issue 9 (21st January 2020) - Taricska, Nóra; Horváth, Dániel; Menyhárd, Dóra K.; Ákontz‐Kiss, Hanna; Noji, Masahiro; So, Masatomo; Goto, Yuji; Fujiwara, Toshimichi; Perczel, András
Abstract : Studying the early phases of amyloid formation is of crucial importance both for understanding the initialization of various pathophysiological processes and for aiding the design of non‐toxic peptide medications that will not become initiators of such processes themselves. This work reports a new monitoring technique using ECD measurements of amyloid progression that can be applied even if the amyloid in question is ThT silent. The amyloid buildup of an Exenatide (in treatment for Type II Diabetes Mellitus ) derivate miniprotein (E5) is monitored on a simplified hyperspace, using spectroscopic and molecular modeling techniques. More information can be found in the Full Paper by A. Perczel et al. on page 1968 .